Necroptosis and Viral Myocarditis: Tumor Necrosis Factor α as a Novel Biomarker for the Diagnosis of Viral Myocarditis - Zhou, Jin; Xu, Jing; Li, Peng; Sun, Shan; Kadier, Yimiti; Zhou, Shiying; Cheng, Aijuan (Frontiers in Cell and Developmental Biology, 2022)
Programmed cell death (PCD) including necroptosis is associated with the induction of inflammation. Tumor necrosis factor-alpha (TNF-α) is an important cytokine involved in the activation of necroptosis. In this review, we summarized and evaluated the available evidence on the pathogenesis, molecule mechanism, diagnosis and potential treatment strategies of acute myocarditis, with a special focus on the novel mechanism of necroptosis and virus-induced and virus-associated myocarditis. To explore the clinical implication of TNF-α, we subsequently conducted a meta-analysis on the efficacy of serum TNF-α expression level and its diagnostic accuracy on acute viral myocarditis detection. Further, we identified knowledge gaps, appraise the available experimental models and propose future directions for the relation of necroptosis and myocarditis.